2011
DOI: 10.1038/jhg.2011.85
|View full text |Cite
|
Sign up to set email alerts
|

HRAS mutants identified in Costello syndrome patients can induce cellular senescence: possible implications for the pathogenesis of Costello syndrome

Abstract: Costello syndrome (CS) is a congenital disease that is characterized by a distinctive facial appearance, failure to thrive, mental retardation and cardiomyopathy. In 2005, we discovered that heterozygous germline mutations in HRAS caused CS. Several studies have shown that CS-associated HRAS mutations are clustered in codons 12 and 13, and mutations in other codons have also been identified. However, a comprehensive comparison of the substitutions identified in patients with CS has not been conducted. In the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 53 publications
(81 reference statements)
0
19
0
1
Order By: Relevance
“…Patients with CS have a 13 % probability of developing tumors. 15 It is caused by heterozygous mutations in the HRAS protooncogene in more than 80 % of cases. 16 Given the overlapping clinical features of these syndromes and their variable expression, molecular testing is critical to establish an accurate diagnosis.…”
mentioning
confidence: 99%
“…Patients with CS have a 13 % probability of developing tumors. 15 It is caused by heterozygous mutations in the HRAS protooncogene in more than 80 % of cases. 16 Given the overlapping clinical features of these syndromes and their variable expression, molecular testing is critical to establish an accurate diagnosis.…”
mentioning
confidence: 99%
“…The MAPK pathways are critical downstream mediators of RAS signal transduction, and have been shown to be upregulated in response to oncogenic HRAS mutations in Costello syndrome. 8,18,38,39 Thus, C7669 fibroblasts were treated with inhibitors of the MAP-kinases Erk (PD98059), p38 (SB203580) and SAPK/JNK (SP600125) for 48 h, and subsequently analyzed for C4ST-1 mRNA expression by qRT-PCR (Figure 2n). Blocking all three MAPK cascades was able to significantly elevate the C4ST-1 expression by approximately 2-to 3.5-fold when compared with a DMSO-treated control.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, cellular senescence was reported in fibroblasts with forced expression of HRAS-activating mutations. 39 Strikingly, we previously demonstrated that mice homozygous for a C4st-1 loss-of-function …”
Section: Discussionmentioning
confidence: 99%
“…In years since, the situation has become less clear. Consider that some of the germline mutations in the RASopathy Costello syndrome occur at codon 12 [29] which is also the most common codon mutated in RAS mutations found in cancer [30]. Our analysis demonstrates that the quantity of mutant expressed is an important variable for determining signal strength.…”
Section: A Spectrum Of Ras Strengthsmentioning
confidence: 87%